When Rome ruled [videorecording] - Oliver, Dan; Silvester, Olwyn; Poor, Bray; National Geographic Society (U.S.); Vivendi Entertainment (Firm) ([United States] : National Geographic ; Universal City, Calif. : Distributed by Vivendi Entertainment)
"6-part series reveals ... [an] up-to-date vision of the ancient empire and challenges our perception of what we know about the Romans and their lives. New discoveries about the Roman gladiators, Pompeii doomsday, and Caesar's assassination provide fresh insights into the empire that not only influenced Western civilization, but created it"--Container